2020
DOI: 10.3390/genes11030302
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis Identifies LINC00152 as a Biomarker of Early Relapse and Mortality in Acute Lymphoblastic Leukemia

Abstract: Evidence showing the role of long non-coding RNAs (lncRNAs) in leukemogenesis have emerged in the last decade. It has been proposed that these genes can be used as diagnosis and/or prognosis biomarkers in childhood acute lymphoblastic leukemia (ALL). To know if lncRNAs are associated with early relapse and early mortality, a microarray-based gene expression analysis in children with B-lineage ALL (B-ALL) was conducted. Cox regression analyses were performed. Hazard ratios (HR) and 95% confidence intervals (95%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…When comparing ID to REL samples within each subtype studied, 570, 113, and 248 lncRNAs were differential in DUX4 , Ph-like, and in NH-HeH samples respectively. Other studies have shown that LINC00152 and LINC01013 were among the most differentially expressed genes in patients with early relapse of disease compared to healthy controls [ 76 ]. Specifically, higher expression of LINC00152 in children with B-ALL was associated with a higher risk of early relapse; conversely, lower expression of LINC01013 was associated with early relapse.…”
Section: Long Non-coding Rnas In Progenitor B-cell Acute Lymphoblamentioning
confidence: 99%
“…When comparing ID to REL samples within each subtype studied, 570, 113, and 248 lncRNAs were differential in DUX4 , Ph-like, and in NH-HeH samples respectively. Other studies have shown that LINC00152 and LINC01013 were among the most differentially expressed genes in patients with early relapse of disease compared to healthy controls [ 76 ]. Specifically, higher expression of LINC00152 in children with B-ALL was associated with a higher risk of early relapse; conversely, lower expression of LINC01013 was associated with early relapse.…”
Section: Long Non-coding Rnas In Progenitor B-cell Acute Lymphoblamentioning
confidence: 99%
“…Previous studies regarding the transcriptic results of B-ALL patients have identi ed a number of lncRNAs and vital protein-coding genes that are associated with the etiology or clinical outcome of B-ALL [17][18][19]. To the best of the authors' knowledge, although some studies have performed transcriptome pro le analysis to investigate the role of lncRNA in the pathogenesis of B-ALL, the small sample sizes of parallel their controls and the restricted numbers of isolated cell types limited the general conclusions of these studies [20][21][22]. Moreover, microarray data prevented the identi cation of novel transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…MLL rearranged, hypodiploid, BCR/ABL fusion gene and high end-induction MRD are the common risk factors for relapse in childhood ALL patients ( 19 ). And several published articles showed that the biomarkers for early recurrence in B-ALL include the persistence of MRD, chromosome 19p13 translocations, upregulation of nucleotide excision repair genes, deletion of CDKN2A/B and overexpression of LINC00152 ( Supplementary Table S1 ) ( 20 24 ). In this study, we looked for genes involved in early relapse of B-ALL on a larger sample.…”
Section: Discussionmentioning
confidence: 99%